KEPEMIMPINAN KEPALA MADRASAH DALAM MEMBANGUN IKLIM SEKOLAH DI MADRASAH ALIYAH AL-WASHLIYAH 49 KABUPATEN ASAHAN - Imran Imran (Jurnal Al-Fatih, 2021)
This study analyzes the leadership of the head of the madrasah in building a school climate, and the role model of the head of the madrasah in building a school climate in the private Al Washliyah 49 Madrasah Aliyah, Asahan Regency. This type of research is a qualitative research approach, through observation, interviews, and document review. This method is used for several considerations, first adjusting this method is easier when dealing with reality. Second, this method directly presents the nature of the relationship between researcher and respondent. Third, this method is more sensitive and can adapt to a lot of sharpening the joint influence on the value patterns faced. The targets of the interviews / respondents in this study included the head of madrasah, deputy head of madrasah, and teachers and all madrasah members. The formulation of the research problems are 1) What is the type of leadership of the head of the madrasah in building a school climate in Madrasah Aliyah Al-Washliyah 49, Asahan Regency; 2) How is the exemplary leadership of the head of the madrasah in building a school climate in Madrasah Aliyah Al-Washliyah 49, Asahan Regency; 3) How is the interpersonal communication of the head of madrasah in building a school climate in Madrasah Aliyah Al-Washliyah 49, Asahan Regency. The results of the research findings include 1) the type of leadership of the headmaster of a democratic and fatherly madrasah, 2) the exemplary role of the head of the madrasah which is applied including providing maximum service to all school members. 3) In building a school climate in this madrasah, the principal always uses harmonious communication to all school members